HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN PERILAKU DETEKSI DINI PADA PENDERITA KANKER SERVIKS DI RSUP DR. KARIADI SEMARANG TAHUN 2015 - Marta Juwita Situmorang; Sri Winanrni; Atik Mawarni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Cervical cancer is a disease that can be prevented by finding precancerous lesions. One of the checks that can be done to discover precancerous lesions in cervical cancer is the Pap smear or IVA. Based Pusdatin, Ministry of Health of Indonesia in 2013 the prevalence of cervical cancer is highest in the province of Yogyakarta, which is by 4.1%, followed by Central Java as the second rank, ie by 2.1%. RSUP dr. Kariadi a referral center for cervical cancer in Central Java. The purpose of this study was to determine the correlation between knowledge and attitudes to the behavior of early detection of cervical cancer patients at RSUP dr. Kariadi 2015. The method used in this research is explanatory research method with cross sectional study approach. This study population is an estimate of the whole of cervical cancer patients who had been hospitalized during 2015 with a total estimated as many as 417 respondents. 81 sample using sampling technique using consecutive sampling method in which all the subjects that come up and meet the selection criteria and are included in other research within a certain time. The data were analyzed statistically with a significance level of 95%. Results of univariate analysis showed that the highest percentage of patients are aged 45-54 years (40.7%) with a low education level is not completed primary school (30.9%) and elementary school (37.9%), good knowledge (54.3%), and supports attitudes (48.1%). From the chi square test results obtained there was no relationship between knowledge (p=0.054) and attitudes (p=0.061) with the behavior of early detection. From this study it can be concluded that there is no a significant relationship between knowledge and attitudes to the behavior of early detection of cervical cancer patients at RSUP dr. Kariadi 2015